Analisis Return dan Resiko Perusahaan Pengggerak IHSG 2024 Berdasarkan Kapitalisasi Pasar dan Kinerja - Adi Saputra; Hajar Rani Zamzami; Anastasya Dwita.P; Salira Citra Cantika; Putri Fathya (Draf Solusi Indonesia, 2025)
By contrasting the risks and returns of investing in BBRI, AMMN, BBCA, and BBNI shares with the IHSG, this study examines the viability of doing so. The average return and risk (standard deviation) for each stock and IHSG are determined statistically, and beta calculations are used to gauge systematic risk. According to the analysis's findings, the average return of each stock varies from that of the IHSG. Additionally, the standard deviation of risk differs from company to company. One can determine how sensitive these equities are to changes in the market by using beta analysis. While some companies offer larger returns with more manageable risks, others perform less attractively than the JCI. Recommendations for investments are made after weighing risk and return.